2008
DOI: 10.1038/gt.2008.103
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of clinically relevant mutations occurring in lymphoid cells harboring γ-retrovirus-encoded hsvtk suicide genes

Abstract: The in vivo regulation of T lymphocyte activity by the activation of a suicide mechanism is an essential paradigm for the safety of adoptive cell therapies. In light of reports showing that g-retroviral vector-encoded herpes simplex virus thymidine kinase (hsvtk) undergoes recombination, we undertook a thorough investigation of the genomic stability of SFG-based vectors using two variants of the wild-type hsvtk gene. In a large panel of independent clones, we demonstrate that both hsvtk genes undergo recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…[60][61][62][63] Another feature of retroviral vectors is their mutation rate incurred during reverse transcription, which is about 5-fold higher for HIV-1 reverse transcriptase compared with that of Moloney murine leukemia virus (Mo-MLV). [64][65][66][67][68][69] DNA Transposons g-retroviral and lentiviral vectors are complex biological reagents that require expensive biosafety testing and storage. Non-viral approaches would be advantageous, provided that they were as effective.…”
Section: The Vectors G-retroviral and Lentiviral Vectorsmentioning
confidence: 99%
“…[60][61][62][63] Another feature of retroviral vectors is their mutation rate incurred during reverse transcription, which is about 5-fold higher for HIV-1 reverse transcriptase compared with that of Moloney murine leukemia virus (Mo-MLV). [64][65][66][67][68][69] DNA Transposons g-retroviral and lentiviral vectors are complex biological reagents that require expensive biosafety testing and storage. Non-viral approaches would be advantageous, provided that they were as effective.…”
Section: The Vectors G-retroviral and Lentiviral Vectorsmentioning
confidence: 99%
“…Our group has shown that the zeta chain-based CARs could induce strong activation capable of sustaining T-cell proliferation and permitting secondary antigenic restimulation in vitro provided that antigen was presented in the context of CD28-mediated costimulation. 55,59,60 In an effort to determine if T cells-particularly human T cells-expanded in this manner could mediate tumor eradication in vivo and if further in vivo costimulation would be needed to sustain their function, three tumors models using severe combined immunodefıciency-beige/ beige mice were developed that showed that PSMA-targeted T cells could effectively eliminate prostate cancer. T cells were transduced with Pz1, a CAR-targeting human PSMA.…”
Section: Pros Concernsmentioning
confidence: 99%